UKRAINE WITHIN THE WORLD TRENDS OF THE HIGH-TECH PRODUCTS EXPORT MARKET - Alexander Belov (Соціальна економіка, 2022)
Abstract. The article is devoted to the research of world tendencies of the market of export of high - tech products and definition of features of dynamics and place in it of Ukraine. This study notes that the ability to generate and implement its own innovations and produce and improve high-tech goods and services will ensure strong competitiveness of the country, its financial stability and determine its place in the global economic environment of the future.